Desenvolvimento do crisântemo em vasos submetido a diferentes níveis de déficit hídrico no solo - Spadeto, Marjorie Freitas (2016)
Irrigated ornamental plants is growing in Brazil and gaining an importance in the state of Espírito Santo. Generally, these species are sensitives to variation in the levels of water in soil. Hence, it is necessary obtain information that allows to maximi